Incidence of isolated para-aortic lymph node metastasis in early stage endometrial cancer. (November 2019) - Nasioudis, Dimitrios; Holcomb, Kevin
Abstract: Objective: To investigate the incidence of isolated para-aortic lymph node (PaLN) metastasis among patients with stage I endometrial cancer and negative pelvic lymph nodes. Methods: The National Cancer Database was accessed and patients diagnosed between 2004 and 2015 with an endometrial carcinoma limited to the uterus who underwent extensive pelvic lymphadenectomy (defined as at least 10 lymph nodes removed), had negative pelvic lymph nodes, and underwent PaLN sampling/dissection (with at least 5 lymph nodes removed) were selected for further analysis. Comparisons were made with the chi-square test while a binary logistic regression was performed to identify independent predictors of isolated PaLN metastasis. Results: A total of 14398 patients who met the inclusion criteria were identified. Median patient age was 63 years (IQR: 13). Most patients had endometrioid histology (79.8%) and stage IA disease (68.8%). The median number of pelvic LNs removed and examined was 18 (IQR: 10). The median number of PaLN removed and examined was 8 (IQR:5). The overall rate of isolated PaLN metastasis was 1.6%. By binary logistic regression presence of lymphovascular space invasion (OR: 5.38 95% CI: 3.99, 7.24) and substage IB (OR: 2.05, 95% CI: 1.54, 2.73) were associated with the presence of isolated PaLN metastasis. Conclusions: Isolated PaLN in the absence of pelvic lymph node metastasis is extremely rare among patients with stage I endometrial cancer even in the presence of high risk characteristics.